Impact of Corporate Social Responsibility (CSR) Implementation on The Profitability of State-Owned Enterprises: An Analysis of 20 Listed Companies in Indonesia - Febrizal Rahmana (International Journal of Business Studies, 2018)
The purpose ofthis research is to prove that State-Owned Enterprises (SOEs) that invest in CSR will optimize proit in the hope that thesatisfaction of stakeholders is reached effectively. This paper is a quantitative analysis of an exploratory approach. Discusses theimplementation of CSR from 20 state-owned companies is go public companies. This analysis is based on the Global Reporting Initiativereport which provides some aspects of sustainability.The reports were taken from the availability both CSR and inancial data.The nextstep is to look at the EPS trend of these SOEs and comparing to those aspects are applied. The restrictions coverage of this paper is only for20 state-owned companies which listed in Indonesia.In this research proves that the implementation ofCSR has not yet become the burdenofSOEs but can also give the proit growth ofthose SOEs. Where there is a positive relationship between the implementation of CSR and theEarning Per Share (EPS) with coeficient correlation (R) is 0.110, even the tendency ofincreasingly integrated CSR programs grow the proitof SOEs. There is the theoretical implication to management science that the implementation of CSR is not a burdening cost but is aninvestment and CSR is one ofmany ways for companies to increase business competitiveness in the present era. Also, there is themanagerial implication that by implementation CSR is very important to have a mutual beneit between society and corporation while SOEsstill can optimize some proit. This understanding is essential as a high concentration in social and corporate relations in modern times.